Expression deregulation of matrix metalloproteinases and vasoconstriction related genes in Pakistani females with abnormal uterine bleeding - Zertashia Akram; Ishrat Mahjabeen; Faiza Irshad; Malik Waqar Ahmed; Sadaf Rehman; Muhammad Rizwan; Amna Shafqat; Aniqa Kiran; Asma Saeed (BMC, 2022)
Abstract Background Abnormal uterine bleeding (AUB) is irregular menstrual bleeding which has great impact on female health and life style. Various genetic factors are involved in etiology and pathology of AUB. Present study was designed to explore the association of PTGFR, MMP9, MMP2, TGFB3 and VEGFB with AUB. Methods Blood samples of 212 females with AUB were collected along with age-matched healthy control. Expression variation of targeted genes was evaluated using qPCR. Present study cohort was divided into different groups based on demographic parameters and all targeted genes were correlated with study demographics. Results Expression of targeted genes was significantly (P < 0.001) downregulated in females with AUB compared to control. Reduced (P < 0.01) expression of targeted genes was observed in all age groups (21-30, 31-40, 41-50 year) of AUB patients compared to respective control. Expression of VEGFB increased (P < 0.05) in AUB females with > 9 days bleeding compared to AUB patient had < 9 days bleeding. AUB women with miscarriage history showed upregulation in MMP2, TGFB3 (P < 0.05), and downregulation in MMP9 and VEGFB (P < 0.05) expression compared to AUB group with no miscarriage history. Expression of MMP2 increased (P < 0.05) in AUB females with > 60 kg body weigh compared to AUB patient with < 60 kg weight. Conclusion Present study open a new window for diagnosis of AUB at early stages and suggested a possible involvement of PTGFR, MMP9, MMP2, TGFB3 and VEGFB as candidate biomarkers in AUB.